DNMT3a-Mediated Enterocyte Barrier Dysfunction Contributes to Ulcerative Colitis via Facilitating the Interaction of Enterocytes and B Cells - Bo Cheng; Ai-mei Rong; Wenlu Li; Xiuqian Bi; Xinguang Qiu (Mediators of Inflammation)
Objective. Dysfunction of the enterocyte barrier is associated with the development of ulcerative colitis (UC). This study was aimed at exploring the effect of DNMT3a on enterocyte barrier function in the progression of UC and the underlying mechanism. Method. Mice were given 3.5% dextran sodium sulphate (DSS) in drinking water to induce colitis. The primary intestinal epithelial cells (IECs) were isolated and treated with lipopolysaccharide (LPS) to establish an in vitro inflammatory model. We detected mouse clinical symptoms, histopathological damage, enterocyte barrier function, B cell differentiation, DNA methylation level, and cytokine production. Subsequently, the effect of DNMT3a from IECs on B cell differentiation was explored by a cocultural experiment. Result. DSS treatment significantly reduced the body weight and colonic length, increased disease activity index (DAI), and aggravated histopathological damage. In addition, DSS treatment induced downregulation of tight junction (TJ) protein, anti-inflammatory cytokines (IL-10 and TGF-β), and the number of anti-inflammatory B cells (CD1d+) in intestinal epithelial tissues, while upregulated proinflammatory cytokines (IL-6 and TNF-α), proinflammatory B cells (CD138+), and DNA methylation level. Further in vitro results revealed that DNMT3a silencing or TNFSF13 overexpression in IECs partly abolished the result of LPS-induced epithelial barrier dysfunction, as well as abrogated the effect of IEC-regulated B cell differentiation, while si-TACI transfection reversed these effects. Moreover, DNMT3a silencing decreased TNFSF13 methylation level and induced CD1d+ B cell differentiation, and the si-TNFSF13 transfection reversed the trend of B cell differentiation but did not affect TNFSF13 methylation level. Conclusion. Our study suggests that DNMT3a induces enterocyte barrier dysfunction to aggravate UC progression via TNFSF13-mediated interaction of enterocyte and B cells.